ACCULTURATION OF ISLAMIC CULTURE AND TRADITIONS OF THE BASAP DAYAK TRIBE IN THE BUFFER ZONE OF THE NATIONAL CAPITAL CITY (IKN) OF EAST KALIMANTAN: Akulturasi Budaya dan Tradisi Islam Suku Dayak Basap di Wilayah Penyangga Ibukota Negara (IKN) Kalimantan Timur - Norhidayat; Sainal A; Rey Samuel (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Acculturation of Islamic Culture and Traditions of the Basap Dayak Tribe in the Buffer Zone of the National Capital City (IKN) of East Kalimantan. This research aims to analyze the background of the Dayak Basap tribe in East Kutai. Apart from that, this research also reveals the social and economic life of the Dayak Basap tribe and how unique it is for them to live in an environment that is predominantly non-Muslim. The type of research carried out is qualitative research with historical methods. This research aims to analyze the history of the Dayak Basap tribe. This is interesting because the majority of the Dayak tribe adhere to Christianity and Catholicism, but the Dayak Basap tribe is predominantly Muslim. Another thing studied is their socio-economic life. The data collection techniques used are techniques usually used in qualitative research methodology consisting of (observation, interviews, documentation and library research), source criticism. The approach used is Apart from that, the interview guide is also used as an instrument to facilitate data collection in the form of explanations from respondents who are interviewed and are considered competent in their fields.